PENGARUH LEVERAGE DAN UKURAN PERUSAHAAN TERHADAP TAX AVOIDANCE DAN KEPEMILIKAN MANAJERIAL SEBAGAI VARIABEL INTERVENING PERUSAHAAN FARMASI DI BURSA EFEK INDONESIA PERIODE 2015-2019 - Hari Purnama (Medikonis, 2021)
ABSTRACT This study aims to examine the effect of Leverage, Company Size and Managerial Ownership on Tax Avoidance. To test the effect of Leverage and Company Size on Managerial Ownership. To test the effect of Leverage and Company Size on Tax Avoidance which is moderated by Managerial Ownership. The variables of this study consist of independent and dependent variables. The independent variables of this study are Leverage, and Company Size, the dependent variable is Tax Avoidance and Management Ownership moderation variables. The population in this study were all pharmaceutical companies on the Indonesia Stock Exchange for the 2015-2019 period. The sampling technique was purposive sampling. The data collection method uses literature and documentation. The analysis technique used is path analysis or path analysis using multiple linear regression with a significance level of 5%. Leverage has no effect on Tax Avoidance. Meanwhile, Company Size and Managerial Ownership have a positive and significant effect on Tax Avoidance. Leverage has no effect on managerial ownership. Firm size partially has a significant effect on managerial ownership. Managerial Ownership is not able to mediate the effect of Leverage on Tax Avoidance. Managerial Ownership is able to mediate the relationship between the influence of Company Size on Tax Avoidance.